New Microbial Technologies for Advanced Biofuels 2015
DOI: 10.1201/b18525-11
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Structures Differentiated in a Single- Chamber Air-Cathode Microbial Fuel Cell Fueled with Rice Straw Hydrolysate

Abstract: Background: The development of advanced biofuels from lignocellulosic biomass will require the use of both efficient pretreatment methods and new biomass-deconstructing enzyme cocktails to generate sugars from lignocellulosic substrates. Certain ionic liquids (ILs) have emerged as a promising class of compounds for biomass pretreatment and have been demonstrated to reduce the recalcitrance of biomass for enzymatic hydrolysis. However, current commercial cellulase cocktails are strongly inhibited by most of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…For endoglucanases, GH families 5, 7, 12, and 45, and for xylanases, GH families 10 and 11 were represented (Table ). Enzymes of bacterial and fungal origin were involved and special attention was paid to involve enzymes with notable thermostability due to the previously suggested correlation between thermostability and IL tolerance . A miniaturized screening assay was developed to allow high throughput operation and to minimize the use of ILs and enzymes in the screening.…”
Section: Resultsmentioning
confidence: 99%
“…For endoglucanases, GH families 5, 7, 12, and 45, and for xylanases, GH families 10 and 11 were represented (Table ). Enzymes of bacterial and fungal origin were involved and special attention was paid to involve enzymes with notable thermostability due to the previously suggested correlation between thermostability and IL tolerance . A miniaturized screening assay was developed to allow high throughput operation and to minimize the use of ILs and enzymes in the screening.…”
Section: Resultsmentioning
confidence: 99%
“…While most detected proteins were homologous to existing CAZy families, several contained unknown catalytic domains linked to CBMs for cellulose and xylan. In another study, Gladden and colleagues identified thermotolerant and ionic-liquid tolerant cellulases from a microbial community enriched on switchgrass using a combination of metagenomics and expression screening [22 ]. Candidates identified in silico were synthesized and expressed in vitro using an Escherichia coli cell free system and in vivo using a low copy plasmid.…”
Section: Model Organisms and Ecosystemsmentioning
confidence: 99%
“…The FE-SEM images of untreated and IL pretreated AGB were taken at 5,000x and 10,000x magnification ( ; therefore a watching step is necessary to remove residual IL from biomass prior to addition of enzymes [39]. Developing IL-tolerant enzymes and microorganisms to conduct enzyme hydrolysis and microbial fermentation in one bioreactor, or using aqueous IL solutions (20e50% IL) to pretreat biomass and potentially reduce the amount of washing required prior to enzymatic saccharification are some of the current options to make the IL pretreatment more efficient [40].…”
Section: Field Emission Scanning Electron Microscopementioning
confidence: 99%